The features of Philippine English across regions Rey John Castro Villanueva - Villanueva, Rey John Castro (Animo Repository, 2016)
The present dissertation aims at providing a new and innovative investigation of the features of Philippine English across regions. This research provides comprehensive discussions on two things: a) distinctive grammatical features and b) structural and functional features of the three- and four-word English lexical bundles. Furthermore, this study uses one million word corpus that was built using the timed and untimed texts written by Tagalog, Cebuano, Ilocano, and Hiligaynon speakers of English. With regard to distinctive grammatical features, an inventory of features of the grammatical innovation processes in the sentences in the corpus was made. Furthermore, using D Souzas (1998) criteria for considering innovations as accepted features of New Englishes when they meet benchmarks of frequency, systematicity (rule-governedness), and use by educated users of the English language, the researcher focuses on the distinctive grammatical features which, based on carefully applied criteria, can be part of Philippine English across regions. These features consist of superficially creative usages of subject and verb agreement, articles, prepositions, tense, mass and count nouns, and pronoun-antecedent agreement. The results of the investigation showed that some of the creative errors were put forward to be distinctive grammatical features, while some others were not. The three- and four-word English lexical bundles, on the other hand, were retrieved from the corpus using a computer text analysis tool. Moreover, these bundles were further analyzed both structurally and functionally based on the classifications developed by Biber and his colleagues. While more than half of the English lexical bundles found in this study had not been identified before in previous studies, a number of them appeared in the research of some foreign scholars who used academic corpora built by inner circle speakers of English. Interestingly, all the lexical bundles obtained from the corpus used in this research fit into the structural and functional categorizations used in this study. It should also be noted that based on the analysis of the results, some of the distinctive grammatical features appeared very frequent in the corpus, while some of them did not. This discrepancy may be due to three possible reasons: (a) the interference of Philippine languages in using English (b) the linguistic background (e.g. exposure to English) of the informants and (c) the size of the corpus. On the other hand, the results of the Chi-square Test computations revealed that there were significant differences between and among the Englishes used by Tagalog, Cebuano, Ilocano, and Hiligaynon speakers in terms of prepositional usage innovations, article usage innovations, verb tense usage innovations, and structural features of English lexical bundles. For the mass and count nouns innovation and functional features of English lexical bundles, the results of the calculations revealed that there were no significant differences between and among the Englishes used by the Tagalog, Cebuano, Ilocano, and Hiligaynon speakers. It should also be noted that although, the study does not depart radically from what Bautista (2000) has found, it may contribute to Philippine English research in that the features that Bautista found in her corpus, are also found in the regions. However, this does not necessarily indicate that there are already established regional varieties of English as more research is needed, especially in the phonological features of Philippine English. Lastly, this research lacks spoken material and is based on ostensibly limited data from four groups only Tagalog, Cebuano, Ilocano, and Hiligaynon speakers of English. The future availability of a larger corpus, particularly incorporating spoken material, will facilitate further studies on Philippine English across regions.